Steady-State Analysis of Hybrid Synchronous Machine With Higher Reluctance to Excitation Power Ratio - E. O. Agbachi; L. U. Anih; E. S. Obe (Iranian Journal of Electrical and Electronic Engineering, 2022)
The paper presents the steady-state analysis of a new hybrid synchronous machine with a higher reluctance to excitation power ratio. The machine comprises a round rotor and a salient-pole machine elements that are mechanically coupled together and integrally wound. In each stator, there are two sets of identical poly-phase windings identifiable as the primary and secondary windings which are electrically isolated but magnetically coupled. The primary windings are connected in series between the two sections of the hybrid machine while the secondary windings are connected in anti-series and terminated across a balanced capacitor bank. The hybrid machine exhibits a special feature that when running at the synchronous speed, its effective XD/XQ ratio can be amplified and hence its output by the tuning of the variable capacitance bank which capacitive reactance XC neutralizes only the quadrature axis reactance XQ while the direct axis reactance XD remains unaffected. It is shown that at XD/XQ = 3, the reluctance component of the output power is 2.5 times the excitation power. The calculated and the measured results from the machine are in good conformity.